Gazetteer of military levies from the City of London, 1509-1603 - Archer, I (2001)
This gazetteer lists all levies of troops and ships from the city of London from 1509 to 1603, and attempts costings of each levy. It should be read in conjunction with the author's article, 'The Burden of Taxation on Sixteenth-Century London', published in The Historical Journal, 44:3 (2001), 599-627, where the methodology is more fully explained. Details given in the gazetteer include the crown's requirements, equipment, administration, and financing. It is of use to historians of the military, local government, and taxation.